Critical appraisal of laparoscopic lavage for Hinchey III diverticulitis - Gervaz, Pascal (World J Gastrointest Surg, 2016)
Laparoscopic lavage and drainage is a novel approach for managing patients with Hinchey III diverticulitis. However, this less invasive technique has important limitations, which are highlighted in this systematic review. We performed a PubMed search and identified 6 individual series reporting the results of this procedure. An analysis was performed regarding treatment-related morbidity, success rates, and subsequent elective sigmoid resection. Data was available for 287 patients only, of which 213 (74%) were actually presenting with Hinchey III diverticulitis. Reported success rate in this group was 94%, with 3% mortality. Causes of failure were: (1) ongoing sepsis; (2) fecal fistula formation; and (3) perforated sigmoid cancer. Although few patients developed recurrent diverticulitis in follow-up, 106 patients (37%) eventually underwent elective sigmoid resection. Our data indicate that laparoscopic lavage and drainage may benefit a highly selected group of Hinchey III patients. It is unclear whether laparoscopic lavage and drainage should be considered a curative procedure or just a damage control operation. Failure to identify patients with either: (1) feculent peritonitis (Hinchey IV); (2) persistent perforation; or (3) perforated sigmoid cancer, are causes of concern, and will limit the application of this technique.